El Excentrico, 1972-02-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
February 5, 1972 [5 de febrero de 1972]. No volume or issue. Cover has a photograph of Janie Sanchez, a stewardess for Western Airlines